Reproducción de Anchovia clupeoides y Anchoa parva (Pisces: Engraulidae) en dos ciénagas del Caribe colombiano - Caselles Osorio, Aracelly; Acero P, Arturo (Revista de Biología Tropical, 1996)
From February 1992 to March 1993 sorne reproductive aspects of the fishes A. clupeoides and A. parva were studied at the Ciénaga Grande de Santa Marta and Ciénaga de Pajaral, Colombian Caribbean. The frequent presence of juveniles and mature adults through the year indicate a permanent spawning. The reproductive seasons. determined by the Gonadosomatic Index (GSI), vary according to the monthly behavior of the dominant environmental conditions. The estimation of a Relative Gonadosomatic Index (RGO may be an altemative in order to eliminate the bias shown by the traditional IGS. The condition factors of these species were relatively constant dllring the year. The average sizes of maturity of A. clupeoides and A. parva were 15.1 - 16.2 and 4.5 - 4.8 cm, respectively. Females of A. clupeoides were always more abundant than males. and A. parva show values not very much different from equilibrium. Fecundities of these species are relative1y high and their eggs ate elliptical